COMPARISON OF ESTRUS SIGNS IN REPEAT BREEDING CATTLE WITH OVULATORY DISTURBANCE AND NORMAL OVULATION - DAS, P K; DEKA, K C; BISWAS, R K; GOSWAMI, J (The Indian Journal of Animal Reproduction, 2010)
An investigation was conducted to record the behavioural and physical signs at different periodsof estrus in 75 stall fed repeat breeding crossbred cows and heifers of Assam with anovulation, delayedovulation and normal ovulation. Restlessness and bellowing were predominant behavioural signs ofestrus. Animals with delayed ovulation and anovulation had 72.73 a.nd 25.00 per cent incidence ofrestlessness, respectively upto 36 hrs of estrus, while the animals with normal ovulation did not showrestlessness beyond 24 hrs of estrus. Restlessness persisted upto 48 hrs of estrus in a smallpercentage of animals (9.09) with delayed ovulation. Bellowing was observed till 24 hrs of estrus inanimals with anovulation, delayed ovulation and normal ovulation. At 12 and 24 hrs post onset ofestrus, the percentage of animals showing bellowing was higher with delayed ovulation (100.00 and50.00) and anovulalion (90.00 and 10.00) than with normal ovulation (78.79 and 6.06). Bellowing persistedupto 36 hrs after the onset of estrus in animals with delayed ovulation. Among the physical signs ofestrus, swelling of vulva was found in higher percentage of animals with both delayed ovulation ( 100.00and 95.45) and anovulation (100.00 and 65.00) as compared to normal ovulation (87 .88 and 18.18) at24 and 36 hrs post onset of estrus, respectively. Animals with delayed ovulation (36.36%) and anovulation(5.00%) showed swelling of vulva till 48 hrs of estrus while no animal with normal ovulation had beyond36 hrs of estrus. The number of animals showing pink colouration of the vaginal mucous membranewas higher with delayed ovulation (59.09%) and anovulation (25.00%) as compared to normal ovulation(9.09%) at 48 hrs after onset of estrus. Thin consistency of the vaginal mucus was found to be morenumber in animals with delayed ovulation (81.82%) and anovulation (60.00%) at 12 hrs after onset ofestrus, while most of the animals with normal ovulation (64.52%) had thick consistency of the vaginalmucus during the same period.
Keywords: Repeat breeding; Crossbred cattle; Ovulatory distr~nbances; Behavioural and Physical